Effect of Various Growth Medium on the Physiology and De Novo Lipogenesis of a Freshwater Microalga Scenedesmus rotundus-MG910488 under Autotrophic Condition - Rishibha Dixit; Surendra Singh; Manoj Kumar Enamala; Alok Patel (Clean Technologies, 2022)
The microalga Scenedesmus rotundus, isolated from Jabalpur, Madhya Pradesh, India was designated as Scenedesmus rotundus-MG910488 after morphological and molecular identification. In this study, the effects of various autotrophic growth media on the physiology and lipid accumulation of this microalga were investigated. The cell density, amount of photosynthetic pigments, the productivity of biomass and lipid content and the cell morphology of the microalga were shown to be significantly affected by the variation in growth media. The highest biomass of 754.56 ± 14.80 mg L−1 with biomass productivity of 37.73 ± 0.74 mg L−1 day−1 was achieved when this microalgae was cultivated in the Zarrouk’s medium, whereas the highest lipid content of 33.30 ± 1.21% was observed in the BG-11 medium. The results confirm that the BG-11 is a cost-effective and efficient growth medium for this microalga. It also shows that the ingredients of the growth medium and its concentration influence the growth and synthesis of biomolecules produced by microalga. The biodiesel produced from obtained lipids was qualitatively estimated by Gas Chromatography-Mass Spectroscopy (GC-MS), Nuclear Magnetic Resonance (1H, 13C NMR) and Fourier Transform-Infrared Spectroscopy (FT-IR), which indicate the presence of oleic acid methyl ester, linoleic acid methyl ester and palmitic acid methyl ester as the leading fatty acid methyl esters (FAME) in the samples, which make this strain an ideal feedstock for biodiesel production.